Aflatoxin M1Contamination in Pasteurized Milk in Mashhad, Iran: Aflatoxin contamination of milk - Gholamreza Karimi; Mohammad Hassanzadeh; Marziye Teimuri; Firuzeh Nazari; Amir Nili (Iranian Journal of Pharmaceutical Sciences, 2007)
The aim of this study was to evaluate aflatoxin M1(AFM1) contamination inpasteurized milk samples in Mashhad, Iran. One hundred and ten milk samples fromdifferent supermarkets were collected during three months in spring and investigatedby Enzyme Linked Immuno Sorbent Assay (ELISA). AFM1was found in 100% ofthe milk samples. About 5.4% of the samples contained AFM1greater than themaximum tolerance limit (0.05 μg/l) accepted by European Union. There was nota significant difference among the mean value of AFM1in three months.